2019
DOI: 10.1002/fsn3.906
|View full text |Cite
|
Sign up to set email alerts
|

Study of a common azo food dye in mice model: Toxicity reports and its relation to carcinogenicity

Abstract: This study was conducted to evaluate the toxic effects of an azo dye carmoisine widely used in foods and to investigate its relation to carcinogenicity. Carmoisine administered into mice orally in four different doses as control, low, medium, and high equivalent to 0, 4, 200, and 400 mg/kg bw, respectively, for 120 days. The key toxicological endpoint was observed including animal body weight, organ weights, hematology, biochemistry, and molecular biology assessment. The body weights of medium‐ and high‐dose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 40 publications
4
28
3
Order By: Relevance
“…In addition to leukocytosis, mice exposed to TZ showed thrombocytosis. Accordingly, the number of platelets increased in adults that received the azo dye carnosine for 120 days, as recently reported by [37]. The authors attributed the increase in platelets to the immune response and supported their hypothesis by the notion that platelets act as circulating sensors linking tissue repair and immune responses [38].…”
Section: Discussionsupporting
confidence: 72%
“…In addition to leukocytosis, mice exposed to TZ showed thrombocytosis. Accordingly, the number of platelets increased in adults that received the azo dye carnosine for 120 days, as recently reported by [37]. The authors attributed the increase in platelets to the immune response and supported their hypothesis by the notion that platelets act as circulating sensors linking tissue repair and immune responses [38].…”
Section: Discussionsupporting
confidence: 72%
“…[38] Studies have shown that the intake of these food colorants to a limited extent is fine, but excess consumption of these will result to children hyperactivity, allergies and intolerance. [39] As a consequence of this, Allura red AC was banned in some European countries. [40] These colorant are also utilized in textile industry for dying purpose, however their presence in the environment may lead to deleterious impact on the aquatic life as during the manufacturing process some percentage of the dye goes to the lakes & rivers in the form of industrial effluent thus causing marine pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the noncovalent bond interaction between dyes and polymeric matrices, dyes are easy to migrate and aggregate leading to color fading of materials, as time goes by. Besides, dyes are usually small organic molecules with azo groups, naphthalenes and so on, which are limited in application in various fields due to their high toxicity to human body (except for a few) and serious environmental pollution in the process of production and use . Therefore, nontoxic and green dyes are of great importance.…”
Section: Introductionmentioning
confidence: 99%